Emerging patterns and trends in global cancer burden attributable to metabolic factors, based on the Global Burden of Disease Study 2019 - Zhang, Yan; Ding, Yuwei; Zhu, Ning; Mi, Mi; Lu, Yier; Zheng, Jia; Weng, Shanshan; Yuan, Ying (Frontiers in Oncology, 2023)
Background: The exponential growth of cancer burden attributable to metabolic factors deserves global attention. This research aimed to investigate the trends of cancer mortality attributable to metabolic factors in 204 countries/regions between 1990 and 2019. Methods: We extracted data from the Global Burden of Disease Study (GBD) 2019 and assessed the mortality, age-standardized death rate (ASDR), population attributable fractions (PAFs) in cancers attributable to metabolic factors. The cancer mortality burden was evaluated and stratified according to geographic location, SDI quintiles, age, sex, and its changes over time. Results: Cancer attributable to metabolic factors contributed 865.44x103 (95% UI, 447.97x103-1405.9x103) deaths in 2019, a 167.45% increase over 1990. In the past 30 years, the increase in the number of deaths and ASDR in lower SDI regions has been significantly higher than those in higher SDI regions (from high to low SDIs: the changes of death numbers were 108.72%，135.7%，288.26%，375.34%，288.26% and AAPCs were 0.42%，0.58%，1.51%，2.36%，1.96%).Equatorial Guinea (AAPC= 5.71%), Cabo Verde (AAPC=4.54%), and Lesotho (AAPC=4.42%) had the largest increase in ASDR. Large differences were observed in ASDR of male and female across different SDIs，the male-to-female ratio in ASDR were 1.42,1.50,1.32,0.93,0.86 in 2019.The core population of death in higher SDI regions is the age group of 70 years and above, and the lower SDI regions are concentrated in the age group of 50-69 years. The proportion of premature deaths in lower SDI regions is significantly higher than that in higher SDI regions (from high to low SDIs: 2%, 4%, 7%, 7%, 9%). Gastrointestinal cancers were the core burden，accounting for 50.11% of cancer death attributable to metabolic factors, of which the top three cancers are tracheal, bronchus, and lung cancer, colon and rectum cancer, breast cancer. Conclusions: The cancer mortality burden attributable to metabolic factors is shifting from the higher SDI regions to the lower SDI regions. Gender differences show regional heterogeneity, with males having a significantly higher burden than females in higher SDI regions but the opposite in lower SDI regions. Lower SDI regions have heavier premature death burden. Gastrointestinal cancers are the core to the burden of in cancer attributable to metabolic factors.